Governing climate change: polycentricity in action? - Jordan, Andrew; Huitema, Dave; Asselt, Harro van; Forster, Johanna (Cambridge University Press, 2018)
Governing climate change polycentrically : setting the scene / Andrew Jordan, Dave Huitema, Jonas Schoenefeld, Harro van Asselt and Johanna Forster -- International governance : polycentric governing by and beyond the UNFCCC / Harro van Asselt and Fariborz Zelli -- National governance: the state's role in steering polycentric action / Joana Setzer and Michal Nachmany -- Transnational governance : charting new directions post-paris / Harriet Bulkeley, Michele Betsill, Daniel Compagnon, Thomas Hale, Matthew Hoffmann, Peter Newell and Matthew Paterson -- City and subnational governance: high ambitions : innovative instruments and polycentric collaborations? / Jeroen van der Heijden -- Experimentation : the politics of innovation and learning in polycentric governance / Jan-Peter Vos and Fabian Schroth -- Entrepreneurship : a key driver of polycentric governance? / Elin Lerum Boasson -- Leadership and pioneership: exploring their role in polycentric governance / Duncan Liefferink and Rudiger K. W. Wurzel -- Diffusion : an outcome of and an opportunity for polycentric activity? / Jale Tosun -- Linkages : understanding their role in polycentric governance / Philipp Pattberg, Sander Chan, Lisa Sanderink and Oscar Widerberg -- Orchestration : strategic ordering in polycentric governance / Kenneth W. Abbott -- Policy surveillance : its role in monitoring, reporting, evaluating and learning / Joseph E. Aldy -- Harnessing the market : trading in carbon allowances / Katja Biedenkopf and Jorgen Wettestad -- Decarbonisation : the politics of transformation / Steven Bernstein and Matthew Hoffmann -- Transferring technologies : the polycentric governance of clean energy technology / Liliana B. Andonova, Paula Castro and Kathryn Chelminski -- Governing experimental responses : negative emissions technologies and solar climate engineering / Jesse Reynolds -- Adaptation : the neglected dimension of polycentric climate governance? / Robbert Biesbroek and Alexandra Lesnikowski -- Equity and justice in polycentric climate governance / Chukwumerije Okereke -- Legitimacy and accountability in polycentric climate governance / Karin Backstrand, Fariborz Zelli and Philip Schleifer -- Governing climate change : the promise and limits of polycentric governance / Andrew Jordan, Dave Huitema, Harro van Asselt and Johanna Forster